Genetic and Genomic Analyses of Service Sire Effect on Female Reproductive Traits in Holstein Cattle - Chen, Ziwei; Brito, Luiz F.; Luo, Hanpeng; Shi, Rui; Chang, Yao; Liu, Lin; Guo, Gang; Wang, Yachun (Frontiers in Genetics, 2021)
Fertility and reproductive performance are key drivers of dairy farm profitability. Hence, reproduction traits have been included in the large majority of worldwide selection indexes. Reproductive traits are lowly heritable, but can be improved through direct genetic selection. However, most scientific studies and dairy cattle breeding programs have focused solely on the genetic effects of the dam (GED) on reproductive performance, and therefore, ignored the contribution of the service sire in the phenotypic outcomes. This study aimed to investigate the service sire effects on female reproductive traits in Holstein cattle from a genomic perspective. Genetic parameter estimation and genome-wide association studies (GWAS) were performed for the genetic effect of service sire (GESS) on conception rate (CR), 56-day non-return rate (NRR56), calving ease (CE), still birth (SB), and gestation length (GL). Our findings indicate that the additive genetic effects of both sire and dam contribute to the phenotypic variance of reproductive traits measured in females (0.0196 vs 0.0109, 0.0237 vs 0.0133, 0.0040 vs 0.0289, 0.0782 vs 0.0083, 0.1024 vs 0.1020 for GESS and GED heritability estimates for CR, NRR56, CE, SB, and GL, respectively), and these two genetic effects are positively correlated for SB (0.1394) and GL (0.7871). Interestingly, approximate genetic correlations indicate that GESS on insemination success traits (CR and NRR56) are unfavorably and significantly correlated with some production, health, and type traits (ranging from -0.449 to 0.274), while the GESS on calving traits (CE, SB, and GL) are usually favorably associated with those traits (ranging from -0.493 to 0.313). One-hundred and 62 significant single-nucleotide polymorphisms and their surrounding protein-coding genes were identified as significantly associated with GESS and GED, respectively. Six genes overlapped between GESS and GED for calving traits and 10 genes overlapped between GESS for success traits and calving traits. Our findings indicate the importance of considering the GESS when genetically evaluating female reproductive traits.